Implementasi Perancangan Automatic Watering And Nutrition Plant Berbasis Cam IoT Sebagai Monitoring Smart Farming - Dinda Annura Sukmawati; Asrofi Buntoro, Ghulam; Intan Vidyastari, Rhesma (SinarFe7, 2025)
Agricultural development and food security still face various challenges, one of which is climate change. Extremely hot environmental temperatures in a region impact plant growth, which ultimately has the potential to reduce agricultural productivity. Therefore, an automated system is needed that allows timely watering control to support optimal plant growth. This study aims to design a Cam IoT-based smart farming monitoring system capable of monitoring plant conditions in real-time and remotely. The system is designed using an Arduino Mega microcontroller, an ESP32-CAM camera as an image capture device, and a soil moisture sensor to detect the condition of the growing medium. The obtained data is sent automatically via Telegram as a communication medium between the system and the user. The results of the study showed that the automatic watering pump is only active when the sensor value of the soil condition is dry (value > 750). The system successfully maintains the pH of the growing medium within the ideal range (6.0–7.0) for spinach plant growth. The integration of motion sensors and servos showed 100% success in detecting and responding to pest movements in the agricultural area. In 25 observations, there were 13 motion detections, and all were successfully responded to by moving the servo to a 90° angle. The conclusion of this study is that the IoT Cam-based monitoring system can perform key functions such as monitoring soil moisture and pH, visualizing the planting area, and automatically removing animals. This demonstrates the potential for IoT technology to be applied in smart farming practices, particularly to improve efficiency, productivity, and crop safety in the field.